1998
DOI: 10.1212/wnl.50.6.1746
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of cerebral vasculopathy in patients with Fabry disease

Abstract: These findings provide a predictable outcome measure to assess the effect of molecular interventions on the cerebrovascular circulation in Fabry disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
132
4
5

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(160 citation statements)
references
References 0 publications
18
132
4
5
Order By: Relevance
“…As an earlier study demonstrated an association between cerebral white matter lesions and sleep-disordered breathing [45], the authors accordingly suspected an association between the radiologic findings in their patient and the Cheyne-Stokes breathing disorder [43]. Their conclusion is supported by the fact that severe progressive cerebral white matter lesions are common findings in FD and occur early in the disease process [46] and worsen with time [47].…”
Section: Sleep-related Breathing Disorder and Muscular Involvementmentioning
confidence: 71%
“…As an earlier study demonstrated an association between cerebral white matter lesions and sleep-disordered breathing [45], the authors accordingly suspected an association between the radiologic findings in their patient and the Cheyne-Stokes breathing disorder [43]. Their conclusion is supported by the fact that severe progressive cerebral white matter lesions are common findings in FD and occur early in the disease process [46] and worsen with time [47].…”
Section: Sleep-related Breathing Disorder and Muscular Involvementmentioning
confidence: 71%
“…However, the design of this previous study did not follow each lesion individually, and for this reason it would not be able to detect a disappearance of any lesion at all. As a matter of fact, few other studies on the natural history of CNS impact of FD have been published to date 2,[17][18][19] , and we have already discussed this topic 9 .…”
Section: Discussionmentioning
confidence: 99%
“…In middle age, most males develop cardio or cerebrovascular disease, or both, mainly due to multifocal small vessel involvement 1 . Cranial T2 and fluid attenuated inversion recovery (FLAIR) magnetic resonance imaging (MRI) may show cerebral vasculopathy in the form of multiple hyperintense lesions, typically present in deep gray matter, brainstem, and deep white matter of the hemispheres supplied by the perforating arteries [2][3][4] .…”
mentioning
confidence: 99%
“…Recently, it is reported that cerebral small artery disease, which is known to be associated with lacunar infarction, white matter lesions (leukoaraiosis) and cerebral hemorrhage, rather than large artery stroke, is frequently observed in Fabry's disease. 5,6,20 These findings suggest that the underlying degeneration of the cerebral small arteries, secondary to the deposition of glycosphingolipids in the vessel wall, could be a strong contributing factor for cerebral hemorrhage in Fabry's disease. Aging is thought to be another important contributing factor, 6 as our patients, especially patients 2 (83 years old) and 3 (74 years old), were elderly compared with average Fabry's patients.…”
Section: Discussionmentioning
confidence: 92%
“…1 Stroke is one of the major complications of Fabry's disease 2 and has been described in X25% of patients. [3][4][5][6] In patients with the classic phenotype, levels of a-Gal A activity are very low or undetectable, and progressive glycosphingolipids accumulation leads to renal, cardiac and cerebrovascular manifestations and early death. 1 On the other hand, patients with substantial levels of residual a-Gal A activity have milder phenotypes, including renal 7 and cardiac 8 variant.…”
Section: Introductionmentioning
confidence: 99%